Selecting the Trajectory of the Laser Beam to Form Vias in the Silicon Substrate - A. I. Lapo (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the promising technological directions for the implementation of multi-crystal modules is the assembly of 3D modules. The peculiarity of this technology is the arrangement of the assembly components not only in the horizontal plane, but also vertically. The formation of contact connections between the components of the 3D module can be carried out using wire mounting, as well as using surface mounting technology. To implement the latter, it is necessary to form vias in the silicon wafer. When creating vias between the layers of the multi-crystal module, the focused energy of the laser beam is used. Since the diameter of the holes can be larger than the diameter of the laser beam, it is necessary to move the beam along a given trajectory. To select the trajectory of the focused laser beam, a simulation of the visualization of the laser movement during the formation of a hole for the speeds of 0.5 mm/s and 5 mm/s was carried out. Modeling was performed in COMSOL Multiphysics 5.6, which made it possible to obtain the distribution of thermal fields during laser flashing of holes in the silicon substrate.